Identification of Spen as a Crucial Factor for Xist Function through Forward Genetic Screening in Haploid Embryonic Stem Cells - Monfort, Asun; Di Minin, Giulio; Postlmayr, Andreas; Freimann, Remo; Arieti, Fabiana; Thore, Stéphane; Wutz, Anton (Cell reports, 2015)
In mammals, the noncoding Xist RNA triggers transcriptional silencing of one of the two X chromosomes in female cells. Here, we report a genetic screen for silencing factors in X chromosome inactivation using haploid mouse embryonic stem cells (ESCs) that carry an engineered selectable reporter system. This system was able to identify several candidate factors that are genetically required for chromosomal repression by Xist. Among the list of candidates, we identify the RNA-binding protein Spen, the homolog of split ends. Independent validation through gene deletion in ESCs confirms that Spen is required for gene repression by Xist. However, Spen is not required for Xist RNA localization and the recruitment of chromatin modifications, including Polycomb protein Ezh2. The identification of Spen opens avenues for further investigation into the gene-silencing pathway of Xist and shows the usefulness of haploid ESCs for genetic screening of epigenetic pathways.
Keywords: EZH2 protein; umlčování genů; Haploidy; RNA dlouhá nekódující; jaderné proteiny; DNA vazebné proteiny; RNA, Long Noncoding; haploidie; Embryonic Stem Cells; embryonální kmenové buňky; kultivované buňky; Animals; PRC2; Enhancer of Zeste Homolog 2 Protein; RNA-Binding Proteins; zvířata; myši; Cells, Cultured; Gene Silencing; Polycomb Repressive Complex 2; Mice; Nuclear Proteins; DNA-Binding Proteins; proteiny vázající RNA